2011
DOI: 10.1111/j.1538-7836.2010.04158.x
|View full text |Cite
|
Sign up to set email alerts
|

Succinate independently stimulates full platelet activation via cAMP and phosphoinositide 3‐kinase‐β signaling

Abstract: Summary. Background: The citric cycle intermediate succinate has recently been identified as a ligand for the G-proteincoupled receptor (GPCR) SUCNR1. We have previously found that this receptor is one of the most highly expressed GPCRs in human platelets. Objective: The aim of this study was to investigate the role of SUCNR1 in platelet aggregation and to explore the signaling pathways of this receptor in platelets. Methods and Results: Using real-time-PCR, we demonstrated that SUCNR1 is expressed in human pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 27 publications
2
53
1
5
Order By: Relevance
“…Several authors repeatedly confirmed G i activation by demonstrating a decrease of cAMP levels upon succinate binding to SUCNR1 (Fig. 3), in both heterologous and native systems (Gilissen et al, 2015;Gnana-Prakasam et al, 2011 ;Hakak et al, 2009;Hogberg et al, 2011 ;Sundström et al, 2013). However, the view of SUCNR1 being coupled to G q has been challenged and it was proposed by several authors that the observed [Ca 2+ ] i mobilization was a consequence of PLC-β activation by the βγ dimer (Fig.…”
Section: Succinate Receptor 1 Signaling Pathwaysmentioning
confidence: 78%
See 4 more Smart Citations
“…Several authors repeatedly confirmed G i activation by demonstrating a decrease of cAMP levels upon succinate binding to SUCNR1 (Fig. 3), in both heterologous and native systems (Gilissen et al, 2015;Gnana-Prakasam et al, 2011 ;Hakak et al, 2009;Hogberg et al, 2011 ;Sundström et al, 2013). However, the view of SUCNR1 being coupled to G q has been challenged and it was proposed by several authors that the observed [Ca 2+ ] i mobilization was a consequence of PLC-β activation by the βγ dimer (Fig.…”
Section: Succinate Receptor 1 Signaling Pathwaysmentioning
confidence: 78%
“…In contrast, Robben et al, showed that SUCNR1 is rapidly desensitized and re-sensitized but not internalized in polarized MDCK cells (Robben et al, 2009). Hogberg et al also showed desensitization of SUCNR1 in platelets (Hogberg et al, 2011). The coupling of activated receptor to arrestins 2 and 3 is very weak (Gilissen et al, 2015;Southern et al, 2013).…”
Section: Succinate Receptor 1 Signaling Pathwaysmentioning
confidence: 93%
See 3 more Smart Citations